2022
DOI: 10.1021/acs.est.2c04413
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Enhancement of Lead and Selenate Uptake at the Barite (001)–Water Interface

Abstract: The interactions of heavy metals with minerals influence the mobility and bioavailability of toxic elements in natural aqueous environments. The sorption of heavy metals on covalently bonded minerals is generally well described by surface complexation models (SCMs). However, understanding sorption on sparingly soluble minerals is challenging because of the dynamically evolving chemistry of sorbent surfaces. The interpretation can be even more complicated when multiple metal ions compete for sorption. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 87 publications
1
25
0
Order By: Relevance
“…For example, SrSO 4 has a relatively low mismatch with PbSO 4 and shows F-VdM growth . A similar growth mode was observed for PbSeO 4 on BaSO 4 . However, materials with higher lattice mismatches, closer to that of PbSO 4 on BaSO 4 (such as BaCrO 4 on BaSO 4 and SrSO 4 on BaSO 4 ), tend to form islands.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…For example, SrSO 4 has a relatively low mismatch with PbSO 4 and shows F-VdM growth . A similar growth mode was observed for PbSeO 4 on BaSO 4 . However, materials with higher lattice mismatches, closer to that of PbSO 4 on BaSO 4 (such as BaCrO 4 on BaSO 4 and SrSO 4 on BaSO 4 ), tend to form islands.…”
Section: Resultssupporting
confidence: 70%
“…Thus, the multiple layers of incorporated lead seen by RAXR can be understood as a kinetically determined state involving exchange followed by overgrowth. This is consistent with recent studies on the interaction of Pb–selenate solutions with barite, which also showed a combination of direct exchange and overgrowth . Some additional mechanisms would be needed to understand the apparent lead incorporation into deeper layers, i.e., the third monolayer and below, albeit in a small quantity compared to the top two monolayers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations